231 Utilization of immunotherapy among eligible patients with cervical cancer. (13th November 2020) - Smith, M; Pothuri, B
Abstract : Introduction: Pembrolizumab, a checkpoint inhibitor with a favorable risk/benefit profile, is FDA approved for recurrent or progressive PD-L1 positive cervical cancer treated with prior chemotherapy. The use of pembrolizumab in clinical practice after approval has not been extensively studied. The purpose of this study is to determine frequency of pembrolizumab use among eligible patients with cervical cancer. Methods: This retrospective study includes all patients who underwent surgical procedure or radiation therapy for cervical cancer at an urban private and public hospital system between 5/1/2012 and 1/31/2019 with recurrent or progressive disease after chemotherapy diagnosed after 7/12/18 (date of FDA approval) and PD-L1 positive tumor. Eligible patients were recorded as having received or not received pembrolizumab. Results: Of the 211 cervical cancer patients screened, 21 presented after the date of FDA approval with recurrent or progressive disease and received prior chemotherapy. Twelve (57.1%) patients received PD-L1 testing and 9 (42.9%) potentially eligible patients did not. Eleven patients had PD-L1 positive tumors and were eligible for pembrolizumab. Of eligible patients, 7 (63.6%) received pembrolizumab and 4 (36.4%) did not; 1 was enrolled in a clinical trial and 3 received chemotherapy. Conclusion: Immunotherapy is underused in patients with advanced cervical cancer. Over 40% of patients with progressive/recurrent cervical cancer don't even undergo testing for PD-L1 expression; in those with positive PD-L1 expression only two thirds of patients received pembrolizumab, an FDA approved therapy. There is an opportunity to improve the identification of eligible patients and increase the use of checkpoint inhibitors in cervical cancer.